Kinetic equations for the pseudospin model with barriers - Kovarskii, V.L. (Физика и техника высоких давлений, 2012)
A new formalization of Glauber method is developed and applied to the pseudospin model with barriers. Kinetic equations are derived for this model and numeric solutions in simplest approximations are obtained. Relaxation and kinetic properties of the model are shown to depend on the barrier value as well on the heatingcooling rate. Heating-cooling cycles reveal hysteresis. The relaxation times are determined by the temperature and the barrier value. The relaxation time for the structural order parameter Sz possesses two vertical asymptotes: the first one caused by phase transition, and the second one determined by slowing kinetics at low temperatures. Разработана новая формулировка метода Глаубера, дано ее приложение к псевдоспиновой модели с барьерами. Получены кинетические уравнения для этой модели, а также численные решения в простейших приближениях. Показано, что релаксация и кинетические свойства модели зависят от энергетического барьера и скорости нагрева–охлаждения. Циклы нагрева–охлаждения обнаруживают гистерезис. Времена релаксации определяются температурой и величиной энергетического барьера. Время релакации для структурного параметра порядка Sz обладает двумя вертикальными асимптотами: первая обусловлена фазовым переходом, вторая – замедлением кинетики при низких температурах. Розроблено нове формулювання методу Глаубера, яке застосовано до псевдоспiнової моделі з бар’єрами. Отримано кінетичні рівняння для цієї моделі, а також чисельні рішення у найпростіших наближеннях. Показано, що релаксація й кінетичні властивості моделі залежать від енергетичного бар’єру й швидкості нагрівання–охолодження. Цикли нагрівання–охолодження виявляють гістерезіс. Часи релаксації визначаються температурою та величиною енергетичного бар’єру. Час релаксації для структурного параметра порядку Sz має дві вертикальні асимптоти: перша обумовлена фазовим переходом, друга – уповільненням кінетики за низьких температур.